"Phase Portraits" of Alfven Waves in Magnetospheric Plasma. Issue 6 (10th June 2022) - Leonovich, A. S.; Zong, Q.‐G.; Kozlov, D. A.; Vlasov, A. A.
Abstract: Alfven waves have a very small‐scale radial (across magnetic shells) structure, in an inhomogeneous magnetospheric plasma. This structure is determined by the Alfven wave type. In spacecraft observations, it is difficult to separate local oscillations of the wavefield from oscillations due to the spacecraft crossing the small‐scale transverse structure of such a wave. We propose a new method ("phase portraits") to determine the type of Alfven waves observed onboard. What we call a "phase portrait" of monochromatic Alfven wave are two related plots: (a) radial distribution of the transverse components of the electric or magnetic field of the wave; and (b) radial distribution of the phase shift between these components. In order to construct such a "phase portrait, " we propose using the transverse components of the wavefield as registered onboard a spacecraft crossing the region occupied by the wave. It is demonstrated that the phase shift between the oscillations of the transverse components of the electric/magnetic field in a monochromatic Alfven wave is uniquely related to its radial structure. The transverse structure of the spacecraft‐observed Alfven wave can be determined by plotting the radial dependence of the phase shift between the wavefield transverse components. Comparing this plot to the calculated theoretical "phase portraits" we can select the most appropriate (similar) portrait in order to determine the radial structure and type of the wave. In this paper, "phase portraits" are constructed for most types of ULF monochromatic Alfven waves observed in the Earth's magnetosphere. Key Points: Equations describing the spatial structure of MHD oscillation field in a dipole‐like magnetosphere are derived A method is proposed to determine the radial structure of Alfven waves using phase shifts between transverse components of their field "Phase portraits" are plotted for the main types of monochromatic Alfven waves in the Earth's magnetosphere